Delivering a net zero carbon built environment – Targets and Pathways. Issue 1 (1st December 2022) - He, Bao-Jie; Prasad, Deo
Abstract: Carbon neutrality is expected to address climate change challenges, and its achievement requires the collective efforts of various industries and sectors. The building and construction sector is a big energy consumer and greenhouse gas emitter, providing numerous opportunities for carbon neutrality. This indicates a need for a net zero carbon built environment, although the targets and pathways to it are still unclear. The paper, therefore, aims to address this research gap by reviewing the existing definition of net zero carbon and the targets set by international institutions (e.g., GABC, WorldGBC, RIBA, LETI, and AIA). The paper also defines the principles behind setting the decarbonisation targets, and presents the pathways tailored to the Australian building and construction sector. Overall, this paper is of importance in demonstrating a methodological framework for determining the net zero operational and embodied carbon targets and the associated pathways for decarbonising the built environment. The method is expected to be suitable for many other nations.